Laparoscopic Resection of Pediatric Solid Pseudopapillary Tumors of the Pancreas. Issue 5 (May 2023) - Niec, Jan A.; Ghani, Muhammad O.A.; Hilmes, Melissa A.; McKay, Katlyn G.; Correa, Hernan; Zamora, Irving J.; Lovvorn, Harold N.
Background: Solid pseudopapillary tumors (SPTs) of the pancreas arise rarely in children, are often large, and can associate intimately with splenic vessels. Splenic preservation is a fundamental consideration when resecting distal SPT. Occasionally, the main splenic vessels must be divided to resect the SPT with negative margins, but the spleen can be preserved if the short gastric vessels remain intact (ie, Warshaw procedure). The purpose of this study was to evaluate outcomes of distal pancreatectomy (DP) for SPT in children and to highlight 2 cases of splenic preservation using the Warshaw procedure. Methods: Patients 19 years and younger who were treated at a single children's hospital between July 2004 and January 2021 were examined. Patient characteristics were collected from the electronic medical record. A pediatric radiologist calculated SPT and pre- and post-operative (ie, non-infarcted) splenic volumes. Results: Eleven patients received DP for SPT. Six DPs were performed open and 5 laparoscopically. The spleen was preserved in 3 open and 4 laparoscopic DPs. A laparoscopic Warshaw procedure was performed in 2 patients. Laparoscopic resection associated with less frequent epidural use ( P = .015), shorter time to full diet ( P = .030), and post-operative length of stay ( P = .009), compared to open resection. Average residual splenic volume after the laparoscopic Warshaw procedure was 70% of preoperative volume. Discussion: Laparoscopic DP for pediatric SPT achieved similar oncologic goals to open resection. Splenic preservation was feasible with laparoscopy in most cases and was successfully supplemented with the Warshaw procedure, which has not been previously reported for SPT resection in children.